2015
DOI: 10.1017/irq.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Xenophon's Route Through Babylonia and Assyria

Abstract: TheAnabasisof the Greek historian Xenophon describes the march of a mercenary army in 401–400b.c.from the Aegean coast down the Euphrates to Babylonia, and back up the Tigris to the Black Sea and the Aegean. This paper presents the evidence for the army's route through Babylonia and Assyria, and attempts to resolve the main uncertainties.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, they did not form any reasonable perimeter characteristic of enclosures. Only in one case did the present survey come across traces of undoubtedly ancient remains-the line identified east of the Mahad hills (see Figure 12 and Figure 15), running roughly north-south, accounts for a short stretch of the over-90-km-long Assyrian canal system built by the Assyrian king Sennacherib (704-681 BCE) to bring water from Khinis at the footsteps of the Kurdish mountains to Nineveh [44,[112][113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they did not form any reasonable perimeter characteristic of enclosures. Only in one case did the present survey come across traces of undoubtedly ancient remains-the line identified east of the Mahad hills (see Figure 12 and Figure 15), running roughly north-south, accounts for a short stretch of the over-90-km-long Assyrian canal system built by the Assyrian king Sennacherib (704-681 BCE) to bring water from Khinis at the footsteps of the Kurdish mountains to Nineveh [44,[112][113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that the Mesopotamian water canals could also have been occasionally used for military purposes as barriers [117]. However, given the fact that the Assyrian canal is placed below the Mahad hills, it would have meant placing a military barrier below the uphill positions taken by the Macedonians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation